Writing the City: The Cosmopolitan Realism of Offenbach’s La Vie parisienne - Blaszkiewicz, Jacek (Current Musicology, 2018)
When Offenbach’s La Vie parisienne premiered in Paris in 1866, it entered a longstanding debate on what it meant to be “Parisian.” This article uses La Vie parisienne to explore a key facet of Second Empire modernity: the notion that the Paris was a theater and that its dwellers were actors in a play. The operetta’s title alludes to a popular magazine likewise titled La Vie parisienne, which compared the rituals of Parisians to the scripted behaviors of theatrical characters. The librettists Meilhac and Halévy worked for the magazine in the early 1860s, and subsequently dedicated their operetta to the magazine’s founder, Marcelin. Three co-written vaudevilles reflect Marcelin’s attitudes about urban life and contain the prototypes of La Vie parisienne’s protagonists. As an example of what I call “cosmopolitan realism” in Second-Empire culture, the operetta assumed the function of an operatic anthology—analyzing, taxonomizing, and mythologizing Paris’s spaces, citizens and visitors. Long at the fringes of opera scholarship, operetta and vaudeville provide a rich corpus of literature that aestheticized the industrializing city, contributing to what Offenbach’s contemporaries, such as Charles Baudelaire and Gustave Claudin, diagnosed as la vie moderne.